The effects of medication adherence on study outcomes in randomized clinical trials: A role for cognitive dysfunction?. Issue 6 (2nd November 2021) - Sanborn, V.; Azcarate-Peril, M. A.; Gunstad, J.
Abstract: Medication nonadherence is common and has been associated with poor health outcomes. Older adults are especially likely to be non-adherent to their medications, as they often have more medications to manage and are at greater risk for cognitive dysfunction. Though less frequently examined, the association between cognitive dysfunction and nonadherence also likely extends to clinical trials research. The current study used archival data to examine the potential impact of cognitive dysfunction on adherence to a nutritional supplement as part of a 90-day randomized clinical trial in neurologically healthy middle-aged and older adults. Results showed overall cognitive performance was predictive of adherence to capsule intake when controlling for polypharmacy [ F (1, 157) = 6.53, p < .01]. These results suggest that cognitive dysfunction may impact findings from RCTs through its adverse impact on adherence to study protocol, possibly leading to greater treatment variance, artificially reduced treatment effects, lower study power, and distorted study outcomes and conclusions. A better understanding of methodological and statistical approaches to account for these unwanted effects are needed.